PRELIMINARY TEST FOR CELLULOSE PRODUCTION BY BACTERIA ISOLATED FROM SUGARCANE - Tuya Salas, Jonathan (2021)
Bacterial cellulose has a variety of applications both in the paper, textile, food, cosmetic and medicine industries; This is due to its excellent physicochemical properties such as: high degree of purity, high crystallinity, excellent biodegradability, high Young's modulus, high water retention capacity and excellent biological affinity. The objective of this work was to evaluate cellulose production by bacteria isolated from sugarcane. The collected samples were allowed to ferment until the appearance of a thick film on the surface, from which axenic cultures were obtained on the HS medium. Isolated cultures were transferred to HS brothand incubated under static conditions until a film formed on the culture surface. Bacterial identification was carried out based on a physiological characterization of the isolated strains and their capacity to produce cellulose. FT-IR analysis of the film showed a spectrum corresponding to the characteristic functional groups of bacterial and plant cellulose. The BCP-3,5 strain identified as Komagataeibacter sp. was able to produce bacterial cellulose under static culture conditions.